Micorrização aumenta a tolerância de mudas de Jatropha Curcas L. à salinidade - Oliveira, Dilliani Felipe Barros de (2016)
This study aimed to investigate the association of three species of arbuscular mycorrhizal (AM) fungi (Rhizophagus intraradices; Gigaspora albida and Claroideoglomus etunicatum) with J. curcas, and the effect this symbiosis in developing pre-mycorrhizal seedlings submitted to salt stress at home vegetation. Two experiments were conducted, the first to investigate the association of the fungus to the plant, in a completely randomized design with five treatments (control, isolated species and three inoculated together-MIX) and six repetitions. The second trial was completely randomized blocks in a factorial 4 x 2, with four levels of NaCl (2, 5, 8 and 10 dS / m), and presence or absence of mycorrhizae (MIX), which were evaluated mycorrhizal dependency (MD) and the development of seedlings in salinity soil. The three species of mycorrhizal fungi are associated with J. curcas both in isolation, as when inoculated together. The interaction between these factors showed that the control plants did not differ presence of mycorrhizae, whereas in the saline treatments, pre-mycorrhizal seedlings grew better than non-inoculated. The MD was higher in saline treatments and moderate stress (5 dS / m) provided the best results for this index. Salinity reduced the size of plants, photosynthetic performance, the photosynthetic pigment content, the amount of calcium, potassium, phosphorus and magnesium in the leaves and increased absorption of sodium and chlorine, lipid peroxidation, the activity of antioxidant enzymes and the concentration of proline. Pre-mycorrhizal plants had higher mass, height, stem diameter, number of leaves, leaf area, area ratio pillar, specific leaf area, reduced biomass allocation in leaves and larger, at root, increased root / shoot , higher photosynthetic rate and pigment content, lower activity of antioxidant enzymes, lipid peroxidation reduction, and increased proline content compared to plants not inoculated in the same saline conditions. In seedlings with AMF, high photosynthetic rate, coupled with the large amount of salts in the leaves, the significant increase in proline content and the absence of lipid peroxidation indicates a mechanism mitigating the effect of salinity associated with the presence of mycorrhizae. Therefore, J. curcas seedlings previously mycorrhizal are an alternative to the cultivation of the species under salt stress.